2014
DOI: 10.1021/mp400787s
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Cationic Lipid-Based Nanoparticles Facilitate Endosomal Escape and Reduction-Triggered Cytosolic siRNA Release

Abstract: Small interfering RNA (siRNA) has garnered much attention in recent years as a promising avenue for cancer gene therapy due to its ability to silence disease-related genes. Effective gene silencing is contingent upon the delivery of siRNA into the cytosol of target cells and requires the implementation of delivery systems possessing multiple functionalities to overcome delivery barriers. The present work explores the multifunctional properties and biological activity of a recently developed cationic lipid carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
120
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(123 citation statements)
references
References 45 publications
0
120
0
3
Order By: Relevance
“…Therefore, the following important improvement for this nano-platform is to allow the endosomes to open and release more its cargo into cytoplasm. Previous studies have revealed that modified lipid polymers could enhance the osmolysis of endosomes, such as polyxylitol-based gene carrier XGC [52], distearoyl phosphoethanolamine-polycarboxybetaine (DSPE-PCB) [53], and cationic lipid carrier ECO [54]. To further improve the siRNA delivery capability with this design requirement taken into consideration, we could develop a composite nanocarrier through modified lipid polymers based on our ssRNA-TNP nanosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the following important improvement for this nano-platform is to allow the endosomes to open and release more its cargo into cytoplasm. Previous studies have revealed that modified lipid polymers could enhance the osmolysis of endosomes, such as polyxylitol-based gene carrier XGC [52], distearoyl phosphoethanolamine-polycarboxybetaine (DSPE-PCB) [53], and cationic lipid carrier ECO [54]. To further improve the siRNA delivery capability with this design requirement taken into consideration, we could develop a composite nanocarrier through modified lipid polymers based on our ssRNA-TNP nanosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several novel systems have been designed to conquer multiple barriers for siRNA delivery [22,23]. In spite of the notable improvement attained, none of them fully covered the essential benefits required in extracellular, cellular, and intracellular delivery, which largely limits the clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the notable improvement attained, none of them fully covered the essential benefits required in extracellular, cellular, and intracellular delivery, which largely limits the clinical application. Cationic lipid-based nanoparticles prepared by Gujrati et al [22] have demonstrated desired endosomal escape and reductiontriggered release, but their lack of tumor-targeting capability has limited the in vivo application. The dynamic polyconjugates developed by Rozema et al [23] have successfully combined the functions of passive targeting, active targeting, endosomal escape, and glutathione-sensitive release.…”
Section: Discussionmentioning
confidence: 99%
“…The formulation of nano vehicles for RNAi is critical for the clinical success. Early efforts focused on dendrimer inspired nano constructs and solid nanoparticles (NPs), followed by the biomimetic development of tumor derived exosome-based experimental therapeutics for brain delivery [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The engineering potential of cell type selectivity for these vehicles is limited.…”
Section: Evolving Nano Formulations Of Rnai Expand Therapeutic Potentmentioning
confidence: 99%
“…Multi-targeting capacity is vital for nanoRNAi formulations against patient specific GBM The evolution of nano carriers for siRNAs started with single core solid nano constructs based on classic materials such as gold [24], iron oxide, chitosan [5,17], porous silica [8], sugar [15], solid lipids [3,4,6,9] and an array of dendrimer inspired NPs [12]. Some of these applications showed early promise in effective RNAi of key GBM growth-promoting genes: Jensen et al demonstrated that gold NP mediated siRNA knockdown of the oncoprotein Bcl2Like12 (Bcl2L12) reduced tumor growth [24]; Costa et al demonstrated effective GBM inhibition using anti-miR-21 oligonucleotides, a different approach for tumor promoting miR-21 silencing [4];…”
Section: Evolving Nano Formulations Of Rnai Expand Therapeutic Potentmentioning
confidence: 99%